Letter from Vorstand der Jüdischen Gemeinde, January 1935 - Vorstand der Jüdischen Gemeinde (1935)
Note thanking Max Bredig (1902-1977) for his donation to the Vorstand der Judischen Gemeinde zu Berlin (Aufbringungswerk), or Board of Directors of the Jewish Community in Berlin (funding agency), and a provisional receipt for the payment.
Keywords: Vorstand der Jüdischen Gemeinde; Bredig, Max Albert, 1902-1977; Thank-you notes; Receipts (Acknowledgments); Jewish community centers